BUPRENORPHINE-NALOXONE ABUSE AMONG PARTICIPANTS IN THE NEEDLE EXCHANGE PROGRAMME : A FINNISH TIME-TREND STUDY FROM 2008 TO 2018 - Fältberg, Neea (My University, 2021)
In Finland, buprenorphine is the most common street opioid and buprenorphine-naloxone is widely used in opioid agonist treatment. Studies concerning buprenorphine-naloxone abuse and associated factors are scarce. This research concerns the prevalence and associating factors of buprenorphine-naloxone abuse compared to monobuprenorphine abuse among people who inject drugs attending a needle exchange programme in Turku, Finland. Information on buprenorphine and buprenorphine-naloxone abuse, sociodemographic background, and drug use profile was collected anonymously using questionnaires at four time-points from 2008 to 2018. Data on buprenorphine-naloxone was available in 2008 (n=76, 68%male), 2011 (n=97, 68% male), 2014 (n=103, 57% male), and 2018 (n=97, 56% male). During the 10-year period, both buprenorphine and buprenorphine-naloxone abuse were common: 86%/66% in 2008, 85%/81% in 2011 and 75%/81% in 2014, and 80%/73% in 2018. Of the buprenorphine-naloxone abusers, 85-100% abused also monobuprenorphine. The respective figures for monobuprenorphine abuse without buprenorphine-naloxone abuse varied from 8 to 23% during the 10-year period. Compared to monobuprenorphine abuse, buprenorphine-naloxone abuse associated with amphetamine abuse, methadone abuse, lower education level, attending opioid agonist treatment, and needle sharing. Key conclusions are that buprenorphine-naloxone abuse among people who inject drugs is high in South-Western Finland and buprenorphine-naloxone abuse seems to relate with more disadvantaged drug use profile compared to monobuprenorphine abuse. More effective harm reduction strategies should be aimed for opioid abusers with buprenorphine-naloxone abuse.
Keywords: buprenorphine, buprenorphine-naloxone, abuse, Finland